2005
DOI: 10.1520/jfs2004230
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Mitochondrial DNA Analysis of 691 Casework Hairs

Abstract: A five year retrospective review of mitochondrial DNA (mtDNA) analysis on 691 casework hairs was carried out. A full or partial mtDNA profile was obtained for ã92% of hairs. With increasing age of the hair, the likelihood of obtaining a full profile decreased, although “mini-primer sets” could often be used to capture a partial profile. With increasing color and diameter of the hair, the likelihood of obtaining a profile increased. Full or partial profiles were obtained on more than 80% of 114 hairs ≤1.0 cm. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 11 publications
4
75
1
Order By: Relevance
“…Sekiguchi et al [17] detected 4.4% of heteroplasmy in hair via sequencing and 5.8% when using a sensitive denaturing gradient-gel electrophoresis (DGGE) system. Recently, Melton et al [18] reported point heteroplasmy in 11.4% of forensic casework hairs by sequencing. The rate of heteroplasmy may depend on the methodology used and the parameters used to distinguish heteroplasmy from the noise of the electropherogram.…”
Section: Introductionmentioning
confidence: 99%
“…Sekiguchi et al [17] detected 4.4% of heteroplasmy in hair via sequencing and 5.8% when using a sensitive denaturing gradient-gel electrophoresis (DGGE) system. Recently, Melton et al [18] reported point heteroplasmy in 11.4% of forensic casework hairs by sequencing. The rate of heteroplasmy may depend on the methodology used and the parameters used to distinguish heteroplasmy from the noise of the electropherogram.…”
Section: Introductionmentioning
confidence: 99%
“…In cases with many samples, this will reduce the working time and laboratory expenses. With 91% of hairs showing positive results for mtDNA SNPs (quality criteria "1", "2", or "3"), we had gained a very similar value as [16]. Nevertheless, the qPCR analysis and the subsequent analysis for 32 mtDNA SNPs according to [9], in combination with the recommendations described in this manuscript, take a maximum of 6 μL DNA extract (2 μL for qPCR and at most 4 μL for mtDNA SNP analysis), Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Data points were taken at the beginning (t 0 ), after 1 week (7 days), 1 month (30 days), 3 months (90 days), and 6 months (180 days). The legend on the right side indicates the five different hair donors whereas the protocol of [16] used 10-15 μL without knowing the mtDNA copy number. This study indicates that the detectable mtDNA amount decreases drastically over a time period of 1 month in most of the human hair samples if these are incubated in a warm and wet place.…”
Section: Resultsmentioning
confidence: 99%
“…In a study set of 97 hairs, all morphology-based exclusions were confirmed, but nine of 80 positive associations were excluded by DNA thus firmly establishing mtDNA testing as the preferred method for hair comparisons (Houck and Budowle 2002). MtDNA testing is a very sensitive method and rates of obtaining full or useful partial profiles have been shown to be greater than 90% (Melton et al 2005), with diminishing success for very small fragments (below 0.5 cm) or other types of body hairs (Pfeiffer et al 1999). The high level of sensitivity requires that hair samples are thoroughly decontaminated prior to analysis and that all testing is performed in a contamination-free environment with appropriate controls (Wilson et al 1995).…”
Section: Forensic Dna Databasesmentioning
confidence: 88%